Experiences of nurses and coordinators in a childhood obesity prevention trial based on motivational interviewing within Swedish child health services. Issue 1 (31st December 2022) - Enö Persson, Johanna; Leo Swenne, Christine; von Essen, Louise; Bohman, Benjamin; Rasmussen, Finn; Ghaderi, Ata
ABSTRACT: Purpose: To explore the experiences of nurses and coordinators in the PRIMROSE childhood obesity prevention trial, and to understand the factors that might help to improve the outcome of future primary prevention of obesity. Methods: Using a qualitative approach, data were obtained by interviewing nine intervention nurses and three regional study coordinators. All participants were female. The interviews were transcribed and analysed using content analysis. Results: Two themes emerged: The nurses experienced that it was rewarding to participate in the trial, but challenging to combine the intervention with regular work ; and The study coordinators experienced that they were in a difficult position handling the conflicting needs of the research group and the nurses' commitment to usual child health care services . The importance of support, encouragement, briefer and simpler intervention, and adaptation of the training in motivational interviewing to the setting was emphasized. Stress and lack of time were major barriers to deliver the intervention as intended. Conclusions: Although the PRIMROSE intervention was developed in collaboration with representatives from the child health services, and additional research funding was provided to compensate for time spent working with the trial, nurses experienced stress and time constraints. .